2022
DOI: 10.3847/1538-4357/ac6595
|View full text |Cite
|
Sign up to set email alerts
|

RESOLVE and ECO: Finding Low-metallicity z ∼ 0 Dwarf AGN Candidates Using Optimized Emission-line Diagnostics

Abstract: Existing star-forming vs. active galactic nucleus (AGN) classification schemes using optical emission-line diagnostics mostly fail for low-metallicity and/or highly star-forming galaxies, missing AGN in typical z ∼ 0 dwarfs. To recover AGN in dwarfs with strong emission lines (SELs), we present a classification scheme optimizing the use of existing optical diagnostics. We use Sloan Digital Sky Survey emission-line catalogs overlapping the volume- and mass-limited REsolved Spectroscopy Of a Local VolumE (RESOLV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…In this section, we present the most frequently used classification methods in the optical, showing and discussing where the CLASSY galaxies are located in different diagnostic diagrams. In particular, we compared different criteria to discriminate between ionization processes, sometimes finding that there is no one-to-one agreement in classification, especially for low-mass and low-metallicity galaxies (e.g., Groves et al 2006;Shirazi & Brinchmann 2012;Sartori et al 2015;Nakajima & Maiolino 2022;Polimera et al 2022). In Table 2, we summarize the explored optical diagnostics and the corresponding classifications for each galaxy.…”
Section: Results: Optical Diagnostics Sensitive To the Ionization Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we present the most frequently used classification methods in the optical, showing and discussing where the CLASSY galaxies are located in different diagnostic diagrams. In particular, we compared different criteria to discriminate between ionization processes, sometimes finding that there is no one-to-one agreement in classification, especially for low-mass and low-metallicity galaxies (e.g., Groves et al 2006;Shirazi & Brinchmann 2012;Sartori et al 2015;Nakajima & Maiolino 2022;Polimera et al 2022). In Table 2, we summarize the explored optical diagnostics and the corresponding classifications for each galaxy.…”
Section: Results: Optical Diagnostics Sensitive To the Ionization Sourcementioning
confidence: 99%
“…On the one hand, [N II]/Hα is particularly sensitive to metallicity (Denicoló et al 2002;Kewley & Dopita 2002;Pettini & Pagel 2004;Kewley & Ellison 2008), with lower [N II]/Hα at decreasing metallicity (see, e.g., the CLASSY galaxies J1323-0132 and J0808+3948 in Paper V Figure 2). Since higher [N II]/ Hα line ratios are required to classify galaxies as AGN, the [N II]-BPT by itself is not sufficient for identifying AGN in typical lowmetallicity star-forming z ∼ 0 galaxies (e.g., Groves et al 2006;Reines et al 2020;Molina et al 2021;Polimera et al 2022). For instance, Polimera et al (2022) showed that the [O I]-BPT 38 can identify a theoretical dwarf AGN with a spectrum characterized by ∼90% SF contribution and classified as star-forming according to the [N II]-BPT (see also Hogarth et al 2020).…”
Section: The Classical Optical Bpt Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies triggered a quest for actively accreting intermediate-mass BHs in dwarf galaxies, where they can be detected in large numbers as low-mass (M BH  10 6 M e ) AGN (e.g., see review by Reines 2022). The use of optical spectroscopy has thus far yielded detections of hundreds of AGN in dwarf galaxies and provided estimates of the AGN occupation fraction (taken as a proxy for BH occupation fraction) ranging from <1% (Reines et al 2013;Salehirad et al 2022) to ∼20% (Polimera et al 2022;Mezcua & Domínguez Sánchez 2020. AGN variability studies of large samples of nearby sources are also providing interesting constraints on the local BH occupation fractions (Burke et al 2024).…”
Section: Introductionmentioning
confidence: 99%